Images of Peoples: Two 19th-Century “Ethnographies” of the Habsburg Empire - Slavec Gradišnik, Ingrid (Traditiones, 2024)
In the large-scale book editions on peoples and nations of the multi-ethnic Habsburg Empire during the 19th century, ethnographic topics were often addressed in connection with the pragmatic needs of state administration. Some works adhered to the “land and people” framework, presenting the Empire’s diversity from the perspective of “diversity in unity.” This ideology also underpinned “statistical ethnography,” as exemplified by the works of Karl von Czoernig and Adolf Ficker, which are discussed in this article. These works explicitly engaged with the issue of (multiple) nationalities within a single state, illustrating the close interconnection between science and politics in this context.